Vertical rotor model with hydrodynamic journal bearings. (January 2021) - Pérez, Nicolás; Rodríguez, Cristian
Highlights: This work presents a model for a vertical rotor mounted on hydrodynamic bearing. Model is validated comparing to available experimental studies in the literature model is validated comparing to available experimental studies in the literature. Model predicts the behavior of an actual industrial case with irregular pad clearance. The model developed in this work correctly describes the dynamic behavior of a vertical axis hydrogenerator. Abstract: In hydropower generating plants the reliable operation of the hydropower unit (hydraulic turbine and generator) is a critical issue. Unexpected failure of the hydropower unit lead to high economic costs. A dynamic model of this type of machine is useful for condition monitoring which allows to detect failures in an early stage without the need to stop the machine. Most hydropower units over 20 MW of power has a vertical rotor and are mounted on hydrodynamic journal bearings. In vertical rotors, the load on the bearings is mainly rotatory and to provide stability tilting-pad journal bearings are used. An accurate dynamic model of hydropower unit must consider vertical tilting-pad journal bearings. The present study proposes a dynamic model of hydropower unit that considers the geometrical characteristics of vertical rotor and the behavior of the vertical tilting-pad journal bearing. The dynamic model is validated in two studies found in literature showing good agreement with published data (laboratory vertical rotor and actual hydropower unit). Then, the dynamic model is used to simulate an actual hydropower unit that was operating with an irregular pad clearance. Dynamic model was able to adequately predict waveform, orbits and spectrums of hydropower unit during operation at different power, startup, and during shutdown. It is concluded that dynamic model correctly predicts the failure in the pad clearance.